THE EFFECT OF RICE HUSK BIOCHAR AND NPK FERTILIZER ON THE GROWTH AND YIELD OF RADISH IN RED YELLOW PODSOLIC SOIL - Yopianus Yayat; Darussalam Darussalam; Rini Susana (Jurnal Sains Pertanian Equator, 2022)
Radish (Raphanus sativus L.) is an annual plant, In Podsolic Soil. Utilization red-yellow podsolic soil as a growing medium is fact with the characteristics of dense soil and high clay content, low organic matter content, moderate to high base saturation, generally low nutrient content of N, P, K, and low pH. Efforts to improve the physical and chemical properties of red-yellow podzolic soil can be carried out by giving balanced organic matter and inorganic fertilizers so that it is expected to increase soil productivity. One of the organic materials that can be used was rice husk biochar. NPK anorganik fertilizer is an important macro nutrient needed by plants in large quantities so it must be available in sufficient quantities contain the growing media. This study aims were to find the interaction of biochar and NPK fertilizer on the growth and yield of radish on Red Yellow Podsolik soil. This research was conducted from 27 April – 30 May 2022, in the experimental garden of the Faculty of Agriculture, Tanjungpura University, Pontianak. The study used a factorial Completely Randomized Design (CRD) consisting of 2 factors. The first factor consisted of planting media, namely husk charcoal biochar (A) which consisted of 3 treatment levels and the second factor was NPK fertilizer (P) with 3 treatment levels. Each treatment combination was repeated 3 times and each experimental unit contained 4 sample plants, so there were 108 plants. The variables observed in this study were the number of leaves, plant fresh weight, plant dry weight, tuber length, tuber diameter and tuber fresh weight. The results showed that the dose of 10 tons/ha of biochar and 400 kg/ha of NPK fertilizer gave the best results on the growth and yield of radish on red-yellow podzolic soil. Keywords : Fertilizer, Radish, Rice Husk Biochar, Red-Yellow Podzolic Soil, Response.